2008
DOI: 10.1021/ie800870k
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Solid Residues Obtained from Hot-Compressed-Water Treatment of Woody Biomass

Abstract: Hydrolysis experiment of woody biomass in hot compressed water (HCW) was conducted in a batch-type reactor and the characteristics of solid residue after the HCW hydrolysis treatment were measured to understand the hydrolysis mechanism of woody biomass. Woody slurry of Douglas fir was used in this HCW experiment. Reaction temperature was controlled from 423 to 523 K, and the reaction time was set at 1 min. After separation of solid residues from the hydrolysis liquid material, the solid residue characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 38 publications
5
40
0
Order By: Relevance
“…It was deduced that the macromolecules such as cellulose, hemicelluloses, lignin, and protein broke down into smaller molecules during the procedure treated by hot compressed water [Yuliansyah et al, 2010]. This result agreed with the report obtained from woody biomass, it was found that the solid residue characteristics obtained in HCW changed drastically depending on the reaction temperature [Kobayashi et al, 2009].…”
Section: Resultssupporting
confidence: 88%
“…It was deduced that the macromolecules such as cellulose, hemicelluloses, lignin, and protein broke down into smaller molecules during the procedure treated by hot compressed water [Yuliansyah et al, 2010]. This result agreed with the report obtained from woody biomass, it was found that the solid residue characteristics obtained in HCW changed drastically depending on the reaction temperature [Kobayashi et al, 2009].…”
Section: Resultssupporting
confidence: 88%
“…Meanwhile, a lower solid recovery for 10% solid loading was determined after pretreatment under the same severities. As expected, owing to the enhanced effect on the removal of water-soluble components, the overall solubilization of woody biomass increased under harsher conditions, which is consistent with the trend reported in the literature (Kobayashi et al, 2009;Pérez et al, 2007). Fig.…”
Section: Total Solid Recovery and Ph Change In Hydrolyzatesupporting
confidence: 92%
“…The process in which hot water is used has been referred to as hot water extraction-HWE, also called autohydrolysis (Hsu et al 1988;Schwald et al 1988;Amidon et al 2008), hydrothermolysis (Bobleter and Bonn 1983;Bobleter et al 1991;Hörmeyer et al 1988;Hill 2006;Boonstra and Tjeerdsma 2006;Boonstra 2008;Agbor et al 2011), hot compressed water treatment (Kobayashi et al 2009;Xiao et al 2011), water hydrolysis (Harris 1952), wet torrefaction (Yan et al 2010), hydrothermal carbonization (Funke and Ziegler 2010;Falco et al 2011;Hoekman et al 2011;Libra et al 2011), aqueous fractionation, solvolysis or aquasolv (Agbor et al 2011), aqueous liquefaction (Heitz et al 1986), or cooking (Suchsland et al 1987;Weil et al 1998). This diversity of terms used to describe the same process could hinder comparison of properties of pretreated biomass under the effect of hot water.…”
Section: Thermal Pretreatment Of Wood To Remove Hemicellulosesmentioning
confidence: 99%
“…Wood subjected to HWE showed that important changes occur on the solid residue: particle shape and diameter, as well as pore size changed depending on the reaction temperature (Hietala et al 2002;Kobayashi et al 2009;Duarte et al 2011). The degree of crystallinity as well as liquid wetting and penetration is also increased proportionally to the increase of the severity factor ).…”
Section: Thermal Pretreatment Of Wood To Remove Hemicellulosesmentioning
confidence: 99%